China's international socialization of Caribbean state-society complexes: Trinidad and Tobago as a case study. Issue 2 (4th May 2019) - Tudoroiu, Theodor; Ramlogan, Amanda Reshma
ABSTRACT: Using the case study of Trinidad and Tobago, this article analyzes the process of reciprocal international socialization that allows Beijing to construct a cognitive and normative space conducive to a new regional order in the Caribbean which should be politically friendly, economically profitable, and socially open to its government, companies, and citizens. We argue that there has been a shift in the identity of Trinidad's state-society complex due to the influence of China's very visible political, economic, and social conditionalities. Their impact on political elites (which is reflected in government discourse and actions) and on the society at large (as shown by interviews with 30 Trinidadian nationals) is analyzed in order to show that Type I, 'role playing' socialization has been reached. However, frustration within Trinidad's society with the domestic effects of China's economic and social conditionalities clearly limits the potential for the evolution toward the more advanced Type II socialization exemplified, in the same region, by the Soviet-Cuban relationship. This suggests that, at least in the near future, key features of the Chinese approach incompatible with its self-proclaimed win-win nature will prevent Beijing from upgrading its status to that of a decisive socializer in the Caribbean.